A potential resource for bioconversion of domestic wastewater sludge - Molla , Abul Hossain; Fakhru’l-Razi, Ahmadun; Abd-Aziz, S; Hanafi, M M; Roychoudhury, P K; Alam, Md. Zahangir (Elsevier Science, 2002)
Twenty seven filamentous fungal strains representing five genera; Aspergillus, Penicillium, Trichoderma, Myriodontium and Pleurotus were isolated from four sources; domestic wastewater sludge cake (SC) from IWK (Indah Water Konsortium) wastewater treatment plant, palm oil mill effluent compost from Sri Ulu palm Oil Processing Mill, compost of plant debris, and fungal fruiting bodies from a rotten wood stump. Thirty-three strains/isolates were tested for their ability to convert domestic wastewater sludge into compost by assessing biomass production and growth rate on sludge enriched media. The strains/isolates Aspergillus niger, SST2008, WW-P1003 and RW-Pl 512 produced the highest dry biomass at higher sludge supplemented culture media from their respective group (Aspergillus, Trichoderma, Penicillium and Basidiomycetes, respectively). This implied these strains are better adapted for growth at higher sludge rich substances, and subsequently may be efficient in bioconversion/biodegradation of sludge.The fungi isolated from ecological closely related sources were more amendable to adaptation in a sludge rich culture media.